2011
DOI: 10.1111/j.1439-0388.2011.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping of quantitative trait loci for body weight and bone traits and positional cloning of the RB1 gene in chicken

Abstract: Previously, a quantitative trait locus (QTL) that affects body weight (BW) at 4-12 weeks of age and carcass weight at 12 weeks of age had been mapped on chicken chromosome 1. After including more markers and individuals, the confidence interval was narrowed down to approximately 5.5 Mbps and located this QTL near a microsatellite marker (ADL328). This QTL is the same as the QTL for 12 bone traits, including metatarsus length and metatarsus circumference at 4, 6, 8, 10 and 12 weeks of age and keel length and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
2
21
0
1
Order By: Relevance
“…Linkage disequilibrium: LD was measured as the squared correlation of allele frequencies R 2 , which was affected by both recombination and differences in allele frequencies between sites [33]. The R 2 value between each pair of 29 common SNPs (minor allele frequencies > 0.10) in LoCAD was calculated using Haploview software (http://www.broad.mit.edu/mpg/haploview.html).…”
Section: Nucleotide Diversity and Linkage Disequilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…Linkage disequilibrium: LD was measured as the squared correlation of allele frequencies R 2 , which was affected by both recombination and differences in allele frequencies between sites [33]. The R 2 value between each pair of 29 common SNPs (minor allele frequencies > 0.10) in LoCAD was calculated using Haploview software (http://www.broad.mit.edu/mpg/haploview.html).…”
Section: Nucleotide Diversity and Linkage Disequilibriummentioning
confidence: 99%
“…Intuitively, haplotypes (a block of linked ordered markers) may be more powerful than individual markers [35,36]. In this study, haplotypes were constructed based on a sliding "window" that consisted of three markers; the "window" was allowed to slide one marker at a time ( Figure S3, Table S2) [33]. The haplotypes of each "window" were constructed using the HAPLOTYPE procedure in SAS 9.1.3 software (Chapel Hill, NC, USA).…”
Section: Association Analysismentioning
confidence: 99%
“…were found on chromosome 1 for 12 on bone traits, and the retinoblastoma 1 (RB1) gene has strong relation with bone traits (Zhang et al, 2011). Examination of growth performances on chest width and chest grith helps for the understanding and selection of breeds for the meat production and weight.…”
Section: Comparison Of Tail Feather Length In Ko and Wl Chickensmentioning
confidence: 99%
“…According to Zhang et al (2011), QTL mapping is a major approach to detecting genetic variability of economically important traits. Zhang et al (2010) studied bone traits and identified 12 QTL between LEI0079 and ROS0025 markers on GGA1.…”
Section: Quantitative Trait Loci Mappingmentioning
confidence: 99%
“…The use of advanced techniques for genome studies can be an effective alternative in order to decrease skeletal problems in heavy broilers. Quantitative trait loci (QTL) mapping is one of the major approaches in molecular genetic studies for detecting genetic variability of economically important traits (Zhang et al, 2011). Mapping studies have identified regions in the chicken genome that contribute to characterization of genetic variation, thus allowing mapping of candidate genes.…”
Section: Introductionmentioning
confidence: 99%